2006
DOI: 10.1152/ajprenal.00181.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of the JAK/STAT signaling pathway in diabetic nephropathy

Abstract: Excessive cellular growth is a major contributor to pathological changes associated with diabetic nephropathy. In particular, high glucose-induced growth of glomerular mesangial cells is a characteristic feature of diabetes-induced renal complications. Glomerular mesangial cells respond to traditional growth factors, although in diabetes this occurs in the context of an environment enriched in both circulating vasoactive mediators and high glucose. For example, the vasoactive peptide ANG II has been implicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
174
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(181 citation statements)
references
References 76 publications
(92 reference statements)
6
174
1
Order By: Relevance
“…Owing to its chaperoning function, HSP90 regulates the stability and the activation of NF-kB and STAT signaling pathways by direct association and stabilization of their respective activating kinases, IKK (42) and JAK2 (43). Accordingly, the efficacy of HSP90 inhibitors in animal models has been linked to the disruption of the IKK complex and JAK2 protein stability, further inhibiting downstream transcription factors such as p50/p65 NF-kB (44) and STAT1/STAT3/STAT5 (45). Dysregulated NF-kB and STAT pathways contribute to diabetic nephropathy and atherosclerosis by inducing the transcription of many genes associated with inflammation, renal fibrosis (45)(46)(47), and the proatherogenic state (23,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its chaperoning function, HSP90 regulates the stability and the activation of NF-kB and STAT signaling pathways by direct association and stabilization of their respective activating kinases, IKK (42) and JAK2 (43). Accordingly, the efficacy of HSP90 inhibitors in animal models has been linked to the disruption of the IKK complex and JAK2 protein stability, further inhibiting downstream transcription factors such as p50/p65 NF-kB (44) and STAT1/STAT3/STAT5 (45). Dysregulated NF-kB and STAT pathways contribute to diabetic nephropathy and atherosclerosis by inducing the transcription of many genes associated with inflammation, renal fibrosis (45)(46)(47), and the proatherogenic state (23,48).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the efficacy of HSP90 inhibitors in animal models has been linked to the disruption of the IKK complex and JAK2 protein stability, further inhibiting downstream transcription factors such as p50/p65 NF-kB (44) and STAT1/STAT3/STAT5 (45). Dysregulated NF-kB and STAT pathways contribute to diabetic nephropathy and atherosclerosis by inducing the transcription of many genes associated with inflammation, renal fibrosis (45)(46)(47), and the proatherogenic state (23,48). We have previously tested a number of potential novel approaches (e.g., kinase inhibitors, permeable peptides, and gene therapy) to tackle diabetic nephropathy and atherosclerosis by separately inhibiting the STAT and NF-kB pathways (23,26,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The JAK-Stat3 pathway plays an important role in the pathogenesis of diabetic nephropathy. 34,35 Selective pharmacologic inhibition of JAK2 (AG490) ameliorates nephrotic syndrome in adriamycin-induced nephropathy. 36 Stat3 is also a key mediator in Gas6 nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the microarray data, real-time RT-PCR found that mRNA expression of most Jak/Stat family members remained elevated in glomeruli from progressive diabetic nephropathy patients compared with control samples (Supplementary Table 5A). In the remainder of our study, we focused on Jak-2 since it appears to play a key role in proinflammatory responses in both glomerular and tubular cells (24). Jak-2 mRNA levels were significantly increased in the glomeruli of early diabetic nephropathy patients and in the tubulointerstitium of patients with progressive diabetic nephropathy compared with those of control subjects ( Fig.…”
Section: Jak/stat Pathway In Human Diabetic Nephropathymentioning
confidence: 99%